Job Search Success in Local Labour Markets - A Preliminary Analysis - Malcolm Greig; Ronald W. McQuaid (European Regional Science Association (ERSA), 2001)
This study tests the appropriateness of current government employment policies, in particular the New Deal, in targeting specific groups of unemployed jobseekers. A sample of 169 unemployed jobseekers is divided into those who were successful and unsuccessful in finding employment and each group is analysed in terms of their attributes. A factor analysis of these attributes is then carried out in order to develop typical profiles of unsuccessful jobseekers who are possibly in need of special attention and these are compared with the current New Deal target groups. The findings support the main objectives of the New Deal, in particular the need to support the under 24 age group and the long term unemployed. Some evidence is also found to support targeting jobseekers from deprived areas and lone parents.
Keywords: 330